(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Aloe vera is a perennial, drought-tolerant succulent that belongs to the family Liliaceae, widely valued for its therapeutic, nutritional, and cosmetic properties. The objective of this review is to critically summarize the chemical composition, medicinal properties, and industrial uses of Aloe vera, with emphasis on its major bioactive constituents. A systematic review of peer-reviewed literature, books, and authoritative databases was conducted to compile and synthesize information on phytochemistry, pharmacological activities, and commercial utilization of Aloe vera. The analysis shows that Aloe vera contains numerous biologically active compounds, including saponins, minerals, enzymes, sugars, vitamins, lignin, amino acids, anthraquinones, fatty acids, and polysaccharides. The leaf pulp comprises a complex mixture of enzymes, proteins, lipids, carbohydrates, and inorganic and organic compounds, which collectively contribute to its broad pharmacological profile. Reported studies demonstrate anti-inflammatory, antimicrobial, antioxidant, anti-diabetic, anti-aging, laxative, antitumor, wound-healing, and immunomodulatory activities. Owing to these properties, Aloe vera is extensively incorporated into pharmaceutical formulations, functional foods, nutraceuticals, and cosmetic products for both internal and topical applications. In conclusion, Aloe vera is a multifunctional medicinal plant of considerable therapeutic and commercial significance. Its biological effects are primarily attributed to the synergistic interaction of multiple bioactive compounds rather than a single active principle. However, variability in chemical composition arising from environmental conditions, cultivation practices, and processing methods poses challenges for standardization and quality control. Further well-designed experimental and clinical studies are required to clarify structure–function relationships and to ensure the safe, effective, and standardized utilization of Aloe vera in health-related industries worldwide and future applications.